Penentuan Kadar Kalium Iodat (KIO3) dalam Garam Konsumsi yang Beredar Dipasaran dengan Metode Iodometri - Muthiah Muthiah; Rosliana Lubis; Riyanto Riyanto (Universitas Medan Area, 2020)
Potassium iodide is one of the substances that must be present in iodized salt. The purpose of this research was to determine the level of KIO3 in consumption salts that are circulating in the market by iodometry method based on Indonesia National Standart 01-3556-2016. The results of the reseacrh showed that of the 15 salt sampels, it turns out that 8 salt samples of KIO3 levels meet the SNI standard, which is 30 – 80 ppm, while 7 salt sampels did not meet the SNI Standard. For 7 salt sampels that did not meet SNI standard after testing the moisture content, sodium chloride content and cadmium contamination, only 3 salt sampels of water content meet the SNI standard and 4 sampels of water content did not meet it.For testing the levels of sodium chloride and cadmium contamination, it has met SNI standards.